2016
DOI: 10.15376/biores.11.2.2998-3012
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biobutanol Production from Poplar Wood Hydrolysate using a Mutant of Clostridium saccharobutylicum

Abstract: Enzymatic hydrolysate of poplar wood was used in this study to produce biobutanol by a mutant M-18. Plackett-Burman and Box-Behnken designs were adopted in order to screen crucial factors from various nutrient factors affecting butanol production. These factors included reducing sugar content of hydrolysate, MgSO4•7H2O, yeast extract, K2HPO4, FeSO4•7H2O, CaCO3, and ammonium sulfate. The results demonstrated that a reduction in sugar content, K2HPO4, and CaCO3 were the most critical factors. Yeast extract was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, yeast extract was determined to be outstanding for enhancing the butanol production level from starch wastewater among various nitrogen sources (Luo et al, 2018). In addition, Mao et al (2019) confirmed these findings by evaluating the butanol production of C. acetobutylicum CGMCC1.0134 using fern root as a substrate. When yeast extract was added to the medium, the butanol production increased from 3.74 to 11.8 g/L.…”
Section: Abe Production From C Beijerinckii Cuea02 By Using Sato Wast...mentioning
confidence: 61%
“…Furthermore, yeast extract was determined to be outstanding for enhancing the butanol production level from starch wastewater among various nitrogen sources (Luo et al, 2018). In addition, Mao et al (2019) confirmed these findings by evaluating the butanol production of C. acetobutylicum CGMCC1.0134 using fern root as a substrate. When yeast extract was added to the medium, the butanol production increased from 3.74 to 11.8 g/L.…”
Section: Abe Production From C Beijerinckii Cuea02 By Using Sato Wast...mentioning
confidence: 61%